The evaluation of nutritional composition and functional and pasting properties of wheat flour-coconut flour blends - Makinde, Folasade Maria (Array, 2019)
The feasibility of partially replacing wheat flour with coconut flour in baked products was investigated. Matured coconut (Cocos nucifera) endocarp was grated for the extraction of milk, dried, milled,and pulverized. Five blends of composite flour were prepared by combining wheat flour with 10% to 50% of partially defatted coconut flour,respectively. The 100% wheat flour served as control. The samples were analysed for proximate, mineral, functional,and pasting properties using standard procedures. The proximate analysis indicated 5.52 % moisture, 23.6% protein, 11.14% fibre, 5.4% fat, 5.21% ash,and 49.1% carbohydrate for coconut flour. The ranges of the proximate composition forthe flour blends were:moisture (4.79-5.55%), protein (14.9 -19.1%), fibre (0.44 -5.12%), fat (2.9 -5.3%), ash (0.68-2.13%), carbohydrate (62.7-76.2%),and energy (315.26-335.28 kCal). The values for moisture, protein, fat, fibre,and ash increased with the increasing levels of coconut substitution,except for carbohydrate and energy contents. There were significant differences (p≤0.05) in calcium, magnesium, potassium, phosphorus, iron,and zinc concentrations of the samples. The range of values obtained for these parameters was1.32-2.59 mg/kg, 2.60-3.83 mg/kg, 12.10-16.89 mg/kg, 12.40-18.50 mg/kg,0.50-1.22 mg/kg and 0.30-1.23 mg/kg, respectively. The ranges of functional properties were:loosed bulk density (0.28-0.49 g/mL),packed bulk density (0.44-0.75 g/mL), pH (5.77-6.57), swelling capacity (3.89-6.56%), water absorption capacity (0.89-3.97 ml/g),oil absorption capacity (1.26-3.20 ml/g),and gelation (12.0-18.0%). The pasting characteristics showed significant differences betweenthe100% wheat flour and coconut substituted samples. The results revealed modifications in nutritional, functional, and pasting properties in blends containing fractions of partially defatted coconut flour, which suggests their application in diverse food products.